HUBUNGAN PARITAS IBU BERSALIN DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH DI RSUD dr. MURJANI SAMPIT TAHUN 2017 - arifin mastur (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2018)
Background: The writing of scientific papers is motivated by the percentage of low birth weight babies who maintain their first position of 29% or every day 8.000 of newbord babies in the world die because babies born weighing less than 2500 grams arevery susuceptible to infection (WHO, 2012). Parity effect 30% of the incidence of lowbirth weight babies, according to the assumption that risk parity research is due tohaving children >3 adan 5 times the chance to give birth to low birth weight babies(Henny Juaria, 2014). In preliminary studies conducted by researchers at Hospital dr.Murjani Sampit found 185 babies having low birth weight babies from 2385 number ofbabies born in 2017. Objective: The study aims determine the correlation between maternity parity and theincidence of low birth weight babies in Hospital dr. Murjani Sampit in 2017. Methods: Research method conducted by analiyic survey with a retrospective approach to mothers who gave birth to low birth weight babies and who gave birth to a normalbirth weight baby at Hospital dr. Murjani Sampit in 2017. Conclusion: There is a correlation between maternal parity and the incidence of lowbirth weight babies with p = 0.000 < ? 0.05 (5%), which means mothers with primiparaparity and grandemultipara have a greater risk of giving birth babies compared tomultipara parity.